PELATIHAN PARENTING: PEMAHAMAN SERTA PENGELOLAAN POLA ASUH ANAK TERHADAP TEKNOLOGI DI ERA DIGITAL - Medi Yansyah; Marta Diniyah Putri; Muhammad Renaldi; Daffa Hani Syahirah; Karlina Karlina; Veronica Yulia Putri; Afghan Yuswan (Smart Education, 2024)
Abstract: Parenting training themed “Parenting in the Digital Era” in Sumberejo Village aims to help parents overcome the challenges of educating children in a digital environment. The socialization method was used to deliver information on the impact of technology, screen time management, and effective communication techniques. The results of the training showed positive responses and active discussions from parents in Sumberejo Village with increased awareness of the importance of understanding children's behavior in the digital era. The training successfully provided practical insights and strengthened parents' skills in managing the influence of technology on children. Keywords: Parenting Training, Digital Era, Impact of Technology Abstrak: Pelatihan parenting bertema